TVM, NPV, and IRR, Oh My! Creating an Inclusive Environment for Teaching the Potentially Intimidating Financial Concepts for Making a Real Estate Investment. Issue 1 (31st December 2023) - McGrath, Karen; Worzala, Elaine; Alexander, John
Abstract: This is a pedagogical paper that highlights various techniques that can be used to teach basic real estate finance to a mixed-ability audience, including non-finance majors. We explore some creative ways to engage all levels of students and help them to master the fundamental financial techniques used to understand real estate valuation and investment. In addition, we try to provide instructors with varying levels of financial and real estate experience some alternative modes of delivery for successful teaching outcomes, specifically junior finance professors, instructors or clinical professors who have been hired from the industry, and adjunct professors. We will focus on alternative ways to make the financial analysis portion of an introductory real estate class more relevant and less intimidating to the average student, while endeavoring to retain the interest of finance veterans familiar with these concepts. By using local market information and experiential learning techniques we will demonstrate ways to get students more engaged and excited about these important techniques for analyzing real estate investments, while working to increase confidence in faculty and student alike. Finally, we will examine the choice of tools associated with teaching finance, such as time value of money tables, formulas, financial calculators, and Excel, along with ideas to potentially enhance their effectiveness.